FDR's body politics : the rhetoric of disability - Houck, Davis W. (Presidential rhetoric series, 2003)
Franklin Roosevelt instinctively understood that a politician of his era who was unable to control his own body would be perceived as unable to control the body politic. He therefore took great care to hide his polioinduced lameness both visually and verbally. In FDR's Body Politics, Davis W. Houck and Amos Kiewe draw on never-before-used primary sources to analyze the silences surrounding Roosevelt's disability, the words he chose to portray himself and his policies as powerful and health-giving, and the methods he used to maximize the appearance of physical strength. They examine his broad strategies, as well as the speeches Roosevelt delivered during his political comeback after polio struck, to understand how he overcame the whispering campaign against him in 1928 and 1932. Ultimately, this is a story of triumph and courage that reveals a master politician's understanding of the body politic in the most fundamental of ways.